A broad range of symptoms in allgrove syndrome: single center experience in Southeast Anatolia - GÜRAN, TÜLAY (SPRINGER, 2020)
Background Allgrove syndrome (OMIM 231550) is a rare autosomal recessive disease characterized by non-CAH primary adrenal insufficiency (non-CAH PAI), alacrima, and achalasia. It is caused by mutations in the AAAS gene. The syndrome is also associated with variable progressive neurological impairment and dermatological abnormalities. Methods and results We diagnosed 23 patients from 14 families with Allgrove syndrome, based on the presence of at least two characteristic symptoms, usually adrenal insufficiency and alacrima, between 2008 and 2018. A previously described nonsense variant of AAAS was detected in 19 patients from 12 families at homozygous state. Another novel homozygous mutation (c.394-397delCTGT) in AAAS was detected in four patients from two families. Presenting symptoms were alacrima (23/23; 100%), adrenal insufficiency (18/23; 78%), achalasia (13/23; 57%), short stature/growth retardation (16/23; 70%), hyperreflexia (15/23; 65%), palmoplantar hyperkeratosis (13/23; 57%), hyperpigmentation of the skin (10/23; 43%), hypoglycemia-induced convulsion (7/23; 30%), swallowing difficulty and vomiting (6/23; 26%). Serum DHEAS concentrations were low in all patients (23/23; 100%). Conclusions Clinical symptoms vary even among patients carrying the same mutation. Triple A syndrome should be considered in the etiology of non-CAH PAI in Arab populations and in Southeast Turkey. Any child with non-CAH PAI should be evaluated for the presence of alacrima and/or achalasia or family history of alacrima and/or achalasia. Children with alacrima and/or achalasia should also be investigated for adrenal insufficiency. Definitive molecular diagnosis is essential for early diagnosis and management of adrenal insufficiency, neurological symptoms, and growth retardation in patients and early diagnosis of as yet asymptomatic cases in the family, together with genetic counseling.
Keywords: Triple A syndrome; Allgrove syndrome; Adrenal insufficiency; Achalasia; Palmoplantar hyperkeratosis; Alacrima; TRIPLE-A SYNDROME; PRIMARY ADRENAL INSUFFICIENCY; WD-REPEAT PROTEIN; ADRENOCORTICAL INSUFFICIENCY; 4A SYNDROME; ACHALASIA; ALACRIMA; DEFICIENCY; ALADIN; MANIFESTATIONS